Ethnography: importance, relevance and contributions to nursing care - Banda Pérez, Antonieta de Jesús (2021)
This essay is a review of ethnography and its relationship to nursing care. In the case of ethnography, epistemologically it is about immersing a culture and the art of seeing, learning and interpreting reality in through engagement with participants, either openly or secretly in their environment. Therefore, the role of researchers in data collection is crucial in conducting ethnographic research, as this design will generate rich and deep data. The purpose is to understand the background or phenomena under study and require the researcher to conduct field visits, be reflective and consider their own assumptions and premises to strengthen the research findings. As mentioned by Leiniger, ethno-nursing is considered a qualitative research method that focuses on recording, describing, explaining and interpreting the visions, meanings of the objects of information in a natural, open and inductive way, symbols and experiences. In relation to the context of the COVID-19 pandemic, new ideas have been proposed for researchers who are using ethnographic methods and designing and developing projects. These require reinventing and adjusting their data collection strategies in order to carry out new strategies for implementation. It is concluded that there are different mechanisms to develop ethnography to nursing care and implement this method together with different communities to overcome the various challenges they are currently facing, and it has become the top priority of the needs and requirements of an increasingly diverse cultural society.